Living Islam in Strengthening Sustainable Profit Growth of Islamic Banks in Indonesia - Nofinawati Nofinawati; Saparuddin Siregar; Isnaini Harahap; Adanan Murroh Nasution; Ahmad Maulidizen; Sekar Afifah (JURNAL INDO-ISLAMIKA, 2026)
This study examines how Living Islam strengthens sustainable profit growth in Islamic banks in Indonesia by shaping internal resource management and institutional responses to external economic dynamics. It addresses a key problem in Islamic banking scholarship: profitability has often been explained through financial ratios and macroeconomic variables, while limited attention has been given to how lived Islamic values become organizational capabilities that sustain performance. Using a qualitative interpretive documentary approach, this research analyzes publications, regulatory documents, annual reports, sustainability reports, corporate governance reports, and policy literature through content and thematic analysis. The findings show that Living Islam strengthens profit growth by institutionalizing Islamic values into everyday organizational practices, including ethical governance, value-driven leadership, trustworthy human resource management, prudent asset allocation, operational efficiency, customer-oriented services, and adaptive responses to macroeconomic uncertainty. Internal resources such as capital, human capital, assets, digital infrastructure, ATM networks, and branch offices become stronger organizational capabilities when guided by amānah, iḥsān, shūrā, ʿadl, and maṣlaḥah. External factors such as national economic expansion, oil price volatility, and exchange rate movements are also navigated sustainably when strategic decisions are grounded in Islamic ethical principles. Theoretically, this study extends the Resource-Based View by conceptualizing Living Islam as a value-based organizational capability that transforms resources into sustainable competitive advantage. Practically, it offers strategic insights for Islamic bank managers, regulators, and policymakers to strengthen governance, organizational culture, human resource development, and long-term competitiveness.